2004
DOI: 10.1099/vir.0.80091-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cell death during infectious salmon anemia virus infection is cell type-specific

Abstract: Infectious salmon anemia virus (ISAV) is a very important fish virus in the Northern hemisphere and there is continued interest in understanding the mechanisms of its pathogenesis and persistence in fish. In this study, the permissive fish cell lines SHK-1, CHSE-214 and TO were used to determine whether ISAV-induced cytopathic effect (CPE) is due to apoptosis or necrosis. Characteristic apoptotic DNA fragmentation was observed only in ISAV-infected SHK-1 and CHSE-214 cells. Apoptosis in ISAV-infected SHK-1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 49 publications
4
21
1
1
Order By: Relevance
“…Results of these experiments indicated that during infection with MCMV, HMGB1 release from cells occurs depending on the multiplicity of infection (W. Jiang and D. S. Pisetsky, unpublished observations). Similar results have been obtained by other investigators with West Nile virus and salmon anemia virus infection (46,47). Although virus infection is a complicated event and can involve both apoptotic and necrotic death, our results nevertheless indicate that HMGB1 release may occur during viral exposure, supporting the use of dsRNA as a model.…”
Section: Discussionsupporting
confidence: 92%
“…Results of these experiments indicated that during infection with MCMV, HMGB1 release from cells occurs depending on the multiplicity of infection (W. Jiang and D. S. Pisetsky, unpublished observations). Similar results have been obtained by other investigators with West Nile virus and salmon anemia virus infection (46,47). Although virus infection is a complicated event and can involve both apoptotic and necrotic death, our results nevertheless indicate that HMGB1 release may occur during viral exposure, supporting the use of dsRNA as a model.…”
Section: Discussionsupporting
confidence: 92%
“…2A) support the idea that passively released HMGB1 could contribute to influenza-induced mortality, as has been postulated (26). Local production of HMGB1 via passive release is possible during influenza infections, because other viruses are known to induce HMGB1 leak from infected cells (27)(28)(29). Furthermore, our results using ethyl pyruvate to reduce active secretion of HMGB1 support the notion that active secretion of HMGB1 might occur too late in influenza virus infections to significantly affect mortality (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…It has been speculated that inflammatory responses mediated by active and/or passive release of HMGB1 contribute to pathogenesis of viral infections (Wang et al, 2006). Viruses can induce necrotic cell death and/or trigger inflammatory responses (Chu & Ng, 2003;Fan & Zhang, 1994;Fan et al, 1998;Joseph et al, 2004;Julkunen et al, 2001), which may lead to active and/or passive release of HMGB1. A recent study established that DENV infection elicits passive release of HMGB1 from necrotic epithelial cells infected at high m.o.i.…”
Section: Discussionmentioning
confidence: 99%